Blue Light Regulates Phosphate Deficiency-Dependent Primary Root Growth Inhibition in Arabidopsis - Yeh, Chuan-Ming; Kobayashi, Koichi; Fujii, Sho; Fukaki, Hidehiro; Mitsuda, Nobutaka; Ohme-Takagi, Masaru (Frontiers in Plant Science, 2020)
Plants have evolved mechanisms to improve utilization efficiency or acquisition of inorganic phosphate (Pi) in response to Pi deficiency, such as altering root architecture, secreting acid phosphatases, and activating the expression of genes related to Pi uptake and recycling. Although many genes responsive to Pi starvation have been identified, transcription factors that affect tolerance to Pi deficiency have not been well characterized. We show here that the ectopic expression of B-BOX32 (BBX32) and the mutation of ELONGATED HYPOCOTYL 5 (HY5), whose transcriptional activity is negatively regulated by BBX32, resulted in the tolerance to Pi deficiency in Arabidopsis. The primary root lengths of 35S:BBX32 and hy5 plants were only slightly inhibited under Pi deficient condition and the fresh weights were significantly higher than those of wild type. The Pi deficiency-tolerant root phenotype of hy5 was similarly observed when grown on the medium without Pi. In addition, a double mutant, hy5 slr1, without lateral roots also showed a long primary root phenotype under phosphate deficiency, indicating that the root phenotype of hy5 does not result from increase of external Pi uptake. Moreover, we found that blue light may regulate Pi deficiency-dependent primary root growth inhibition through activating peroxidase gene expression, suggesting the Pi-deficiency tolerant root phenotype of hy5 may be due to blockage of blue-light responses. Altogether, this study points out light quality may play an important role in the regulation of Pi deficiency responses. It may contribute to regulate plant growth under Pi deficiency through a proper illumination.